2012
DOI: 10.1007/s11748-012-0160-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of thymic carcinoma focusing on the possibility of molecular targeted and hormonal therapies

Abstract: Therefore, by examining the expressions of PPARγ and IGF1R, it would be possible to identify therapy-responsive patients and to improve results of thymic carcinoma treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…TLR4 mRNA levels were found to be higher in thymic tissue of non-thymomatous MG patients and thymic tissue adjacent to thymomas compared to thymuses from cardiac surgery patients without MG [69]. The findings on RAGE, HMGB1 and their respective other ligands and receptors may warrant further study in autoimmune disease and cancer to elucidate therapeutic targets [70], [71].…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 mRNA levels were found to be higher in thymic tissue of non-thymomatous MG patients and thymic tissue adjacent to thymomas compared to thymuses from cardiac surgery patients without MG [69]. The findings on RAGE, HMGB1 and their respective other ligands and receptors may warrant further study in autoimmune disease and cancer to elucidate therapeutic targets [70], [71].…”
Section: Discussionmentioning
confidence: 99%
“…LAT1 expression has been intensively investigated in other types of malignancies located such as in the lungs, pancreas, and liver, with results demonstrating that patients with LAT1-immunopositive malignancies have poor prognosis (Kaira et al 2009a(Kaira et al , 2012Li et al 2013;Toyoda et al 2014;Honjo et al 2016). Moreover, to the best of our knowledge, two studies have been presented in English regarding LAT1 and thymic carcinoma, with seemingly controversial results (Kaira et al 2009b;Omatsu et al 2012). These authors considered that LAT1 immunoreactivity was positive only when distinct membrane signal was present.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed cancer-specific LAT1 expression in various organs and also demonstrated poor prognosis of patients with high LAT1 expression levels (Kaira et al 2009a(Kaira et al , 2012Li et al 2013;Toyoda et al 2014;Honjo et al 2016). In regard to thymic carcinoma, two studies have presented seemingly inconsistent results (Kaira et al 2009b;Omatsu et al 2012); namely, Kaira et al (2009b) used an anti-LAT1 polyclonal antibody and demonstrated that LAT1 immunoreactivity was frequently detected in thymic carcinoma but was undetectable in thymoma. On the other hand, Omatsu et al (2012) used an anti-LAT1 monoclonal antibody and reported that LAT1 immunoreactivity was not frequently detected in both thymic carcinoma and thymoma tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…http TCs exhibit specific genetic alterations and appeared to be more aggressive and more likely to relapse and metastasis than thymomas [11,16,17]. Many potential targets have been investigated such as growth factors, cell cycle proteins and molecules belonging to the PI3K/AKT pathway [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%